Epstein-Barr Virus Lacking Glycoprotein gp42 Can Bind to B Cells but Is Not Able To Infect - Wang, Xi (American Society for Microbiology, 1998)
The Epstein-Barr virus gH-gL complex includes a third glycoprotein, gp42, which is the product of the BZLF2 open reading frame (ORF). gp42 has been implicated as critical to infection of the B lymphocyte by virtue of its interaction with HLA class II on the B-cell surface. A neutralizing antibody that reacts with gp42 inhibits virus-cell fusion and blocks binding of gp42 to HLA class II; antibody to HLA class II can inhibit infection, and B cells that lack HLA class II can only be infected if HLA class II expression is restored. To confirm whether gp42 is an essential component of the virion, we derived a recombinant virus with a selectable marker inserted into the BZLF2 ORF to interrupt expression of the protein. A complex of gH and gL was expressed by the recombinant virus in the absence of gp42. Recombinant virus egressed from the cell normally and could bind to receptor-positive cells. It had, however, lost the ability to infect or transform B lymphocytes. Treatment with polyethylene glycol restored the infectivity of recombinant virus, confirming that gp42 is essential for penetration of the B-cell membrane.